Smoking during pregnancy, diet and levels of some micronutrients in adolescents with primary hypertension - Yaneva, Kolarova; Angelova, N., M.; Nedkova, V.; Bozhinova, A.; Gospodinov, K.; Tisheva, S.; Tzonzarova, M. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Primary hypertension frequency in children is determined by cardiovascular risk factors such as obesity, smoking and inappropriate diet. The success of strategies for its prevention is dependent on a plurality of perinatal and postnatal risk factors. THE AIM of this study was to investigate the influence of potential risk factors like maternal smoking during pregnancy and the diet throughout the first year of the child for primary hypertension occurrence and the level of certain trace elements in children with primary hypertension. MATERIAL AND METHODS: The study was conducted among 61 students aged 10-17 years with hypertension and a control group of 20 normotensive children. Maternal smoking during pregnancy and the diet of the infant were determined and studied by conducting a survey. Spectrophotometric methods were used to determine the serum levels of the trace elements Zn, Cu, Cr. The data was processed statistically using Statgraphics. RESULTS: We found that 47.5% of the mothers of children with hypertension had smoked during pregnancy. 80.4% of children with hypertension were formula fed and only 19.6% of them were breast-fed. Significantly lower levels of serum zinc (9,90 ± 1,63 Î¼mol / l) were found in 66.6% of the children with hypertension. Serum copper levels were statistically significantly lower in 50 % of the children (6,76 ± 2,96 Î¼mol / l). All patients with hypertension had significantly lower chromium (0,68± 0,26 Î¼mol / l). CONCLUSION : Smoking mother during pregnancy and formula feeding during the first year of life can probably be considered risk factors for early hypertension manifestation. The status of trace elements Zn, Cu, Cr showed a deficit in children with hypertension. Given the role of these micronutrients in cholesterol metabolism, their low serum levels may lead to early, preclinical vascular changes.